KOLONIALISME DAN PELAKSANAAN REFORMA AGRARIA DI INDONESIA - Damianus Krismantoro (GoAcademica Research dan Publishing, 2021)
This research was carried out with the aim of being able to see how colonialism that occurred to the Indonesian state affected the development of agrarian reform in Indonesia until its implementation at this time. This research will be carried out using normative juridical. The data in this study is secondary data that serves to analyze the problems in this article. The discussion in this study will see how the development of the implementation of the implementation of agrarian reform that occurs in Indonesia from time to time. The results of this study found that the element of colonialism is still attached to the implementation of agrarian reform policy-making in Indonesia. In addition, in overcoming various agrarian conflicts, the Indonesian state still uses the Positive Wettelijk system. This is reflected in the use of state tools in carrying out repressive methods to reduce the conflict. Even though there are regulations issued by the president regarding this agrarian reform, most of the people still have not fully experienced the distribution of land which aims to improve the welfare of the people based on the 1945 Constitution.